Representation of Female Sexuality: Body Celebration in Girl Group (G)I-Dle’s “Nxde” Video Clip (John Fiske Semiotic Analysis) - Dyah Paramitawati; Tri Hastuti Nur Rochimah (Faculty of Leadership & Management, 2024)
E-Proceeding of 4th International Conference on Islam, Media and Communication (ICIMac 2024): “Communication & Digitisation in Madani Society”/ Muhammad Raqib Mohd Sofian, , Siti Suriani Othman, Safiyyah Sabri, Osama Kanaker & Ihab Ahmed Ra’uf Awais. 5th March 2024 Organized by : Faculty of Leadership & Management